Lecturers’ Use of ICTs to implement the Curriculum at a Teacher Training College in Zimbabwe. - Musingarabwi, Starlin (Advances in Social Sciences Research Journal, 2017)
Typical job tasks entailed in implementing a college curriculum such as MS Power presentations in lectures, lecture preparation, research as well as teaching students at a distance require college lecturers in Zimbabwe to use ICTs. In most developed countries lecturers can now integrate ICTs in teaching. In Zimbabwe’s teacher training colleges not much research-based evidence exists about how lecturers cope with the considerably new technologies in their work. This study sought to obtain information on lecturers’ basic use of ICTs as a curriculum innovation that they should embrace in their work. The research employed the mixed-methods research design. I used questionnaires to collect data from a convenience sample of 100 lecturers and conducted interviews with five of the participants. A majority of lecturers indicated that they had irregular access to ICT facilities. They seldom or never used ICTs in their work. Focus group discussions revealed that inadequate ICT facilities including poor internet connectivity contributed to almost non-use of ICTs by most lecturers. Lecturers professed inadequate personal knowledge and skills to use a good number of the technologies. Findings of this study confirm the incidence of unsatisfactory use of basic ICT operations by lecturers at a college with meager functional ICTs. I recommend that the college provides enduring support to enable lecturers to evolve to the stage of proficient use of basic ICT operations for them to ultimately use ICTs for teaching.